Translating Sepsis-3 Criteria in Children: Prognostic Accuracy of Age-Adjusted Quick SOFA Score in Children Visiting the Emergency Department With Suspected Bacterial Infection - van Nassau, Sietske C.; van Beek, Ron H.; Driessen, Gertjan J.; Hazelzet, Jan A.; van Wering, Herbert M.; Boeddha, Navin P. (Frontiers in Pediatrics, 2018)
Background: Recent attempts to translate Sepsis-3 criteria to children have been restricted to PICU patients and did not target children in emergency departments (ED). We assessed the prognostic accuracy of the age-adjusted quick Sequential Organ Failure Assessment score (qSOFA) and compared the performance to SIRS and the quick Pediatric Logistic Organ Dysfunction-2 score (qPELOD-2). We studied whether the addition of lactate (qSOFA-L) would increase prognostic accuracy. Methods: Non-academic, single-center, retrospective study in children visiting the ED and admitted with suspected bacterial infection between March 2013 and January 2018. We defined suspected bacterial infection as initiation of antibiotic therapy within 24 hours after ED entry. Age-adjusted qSOFA, SIRS, qPELOD-2 and qSOFA-L scores were compared by area under the receiver operating characteristics curve (AUROC) analysis. Primary outcome measure was PICU transfer and/or mortality and secondary outcome was prolonged hospital length of stay. Results: We included 864 ED visits (474 (55%) male; median age 2.5years; IQR 9months-6years), of which 18 were transferred to a PICU and 6 ended in death (composite outcome PICU transfer and/or mortality; 23 admissions (2.7%)). 179 (22.2%) admissions resulted in prolonged hospital length of stay. PICU transfer and/or death was present in 22.5% of visits with qSOFA≥2 (n=40) compared to 2.0% of visits with qSOFA<2 (n=444) (p<0.01). qSOFA tends to be the best predictor of PICU transfer and/or mortality (AUROC 0.72 (95% CI, 0.57-0.86) compared to SIRS (0.64 (95% CI, 0.53-0.74), p=0.23) and qPELOD-2 (0.60 (95% CI, 0.45-0.76), p=0.03)). Prolonged hospital length of stay was poorly predicted by qSOFA (AUROC 0.53, 95% CI 0.46-0.59), SIRS (0.49, 95% CI 0.44-0.54) and qPELOD-2 (0.51, 95%CI 0.45-0.57). qSOFA-L resulted in an AUROC of 0.67 (95% CI, 0.50-0.84) for PICU transfer and/or mortality and an AUROC of 0.56 (95% CI, 0.46-0.67) for prolonged hospital length of stay. Conclusion: The currently proposed bedside risk-stratification tool of Sepsis-3 criteria, qSOFA, shows moderate prognostic accuracy for PICU transfer and/or mortality in children visiting the ED with suspected bacterial infection. The addition of lactate did not improve prognostic accuracy. Future prospective studies in larger ED populations are needed to further determine the utility of the qSOFA score.